Effectiveness of Prenatal Yoga Intervention as a Non-Pharmacological Method in Reducing Anxiety in Third-Trimester Pregnant Women at Griya Bundaku - Hidayah, Nurul; Mardiah (International Journal of Clinical Inventions and Medical Sciences (IJCIMS), 2025)
Anxiety in third-trimester pregnant women is a common psychological issue that can negatively impact birth outcomes. Safe and effective non-pharmacological interventions are highly needed to address this problem. Prenatal yoga, as a mind-body intervention, holds great potential, but its effectiveness needs to be scientifically tested in the local context. This study aims to demonstrate the effectiveness of prenatal yoga intervention as a non-pharmacological method in reducing anxiety levels in third-trimester pregnant women at Griya Bundaku. The study used a quasi-experimental design with a pretest-posttest control group design. A total of 30 third-trimester pregnant women who met the criteria were selected using purposive sampling and divided into two groups: 15 respondents in the intervention group (prenatal yoga) and 15 respondents in the control group. Anxiety levels were measured before and after the intervention using the Hamilton Anxiety Rating Scale (HARS) questionnaire. Data analysis was performed using Paired T-Test and Independent T-Test. The results showed a highly significant decrease in average anxiety scores in the intervention group, from 24.5 (moderate anxiety) to 15.2 (mild anxiety) (p < 0.001). Conversely, no significant change was observed in the control group (p > 0.05). The difference test showed that the reduction of anxiety in the intervention group was significantly greater compared to the control group (p < 0.001). Prenatal yoga intervention was proven to be significantly effective in reducing anxiety levels in third-trimester pregnant women. Prenatal yoga is recommended as a safe and beneficial complementary therapy to be integrated into standard prenatal care programs.